Building a System for Telecom Product Development and Operating System Based on Big Data - Jun Zhao; Chenxu Qiu; Renlong He (Dianxin kexue)
With the advent of the era of big data,telecom operators have come to realize that data is the most important strategic resource for an enterprise.Whether it can manage and make good use of data will be the key to success in future cross-sector competition.The existing problems in telecom operator's product development and operating systems were analyzed,and the major changes in telecom operator's direction of product development and operational layout affected by the era of big data were discussed.New concept of data products based on large data,and ideas on reconstruction of carriers product development and operating systems were proposed.Finally the initiative proposal for building telecom product development and operating systems based on large data were given.